Inhibitory effect of helium cold atmospheric plasma on cariogenic biofilms - Figueira, Leandro Wagner [UNESP]; Bessa Muniz, Ana [UNESP]; Doria, Anelise Cristina Osorio Cesar; Castaldelli Nishime, Thalita Mayumi; Kostov, Konstantin Georgiev [UNESP]; Koga-Ito, Cristiane Y. [UNESP] (Taylor & Francis, 2024)
This study aimed to determine the effects of low-temperature plasma jet produced in gas helium (LTP-helium) on cariogenic biofilms composedby Streptococcusmutans, Streptococcus sanguinis and Streptococcus gordonii, and also by the combination of Candida albicans, Lactobacillus acidophilus and S. mutans. Biofilms were treated for 1, 3, 5, and 7 minutes. A 0.12% chlorhexidine solution was used as the positive control and sterile physiologic solution was the negative control. Biofilm viability was analyzed by viable cell recovery, scanning electron microscopy, and confocal laser scanning microscopy. All assays were performed intriplicate in three independent experiments. Multispecies biofilms exposed to LTP-helium had a significant reduction in viability when compared to the negative control (p < 0.0001). For biofilm formedby S. mutans, S. sanguinis, and S. gordonii, LTP treatments for 5 and 7 minutes caused similar reduction of morethan 2 log10. Also, a significant reduction in the viability of biofilms formedby C. albicans, L. acidophilus, and S. mutans was detected (p < 0.0001). In conclusion, LTP-helium reduced theviability of cariogenic biofilms with different microbial compositions, which indicates that LTP-helium is a potential tool for developing new protocols for dental caries prevention and treatment.
Keywords: cariogenic biofilm; Dental caries; low-temperature plasma